2023
DOI: 10.26803/ijlter.22.6.14
|View full text |Cite
|
Sign up to set email alerts
|

Problem-based Learning (PBL) with Reading Questioning and Answering (RQA) of Preservice Elementary School Teachers

Abstract: Preservice elementary school teachers' critical thinking skills were compared during this quasi-experimental study of PBL (Problem-based Learning) and RQA (Reading-Questioning and Answering) science practicum learning. Following the Covid-19 protocol, the science practicum course was completed online in both the PBL and the PBL with RQA. Face-to-face interaction was limited. Blended learning is completed synchronously by Google Meet and asynchronously by Schoology. The science practicum was conducted offline r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Other research also reveals that digital and scientific literacy on genetics topics has increased after being taught using PBL-RQA (Angraini et al, 2023). Similar research was conducted by Leasa et al (2023), which proves that PBL-RQA can improve critical thinking skills in science learning. Therefore, this research aims to determine the effect of PBL-RQA on students' information literacy and selfconfidence.…”
Section: Introductionsupporting
confidence: 60%
“…Other research also reveals that digital and scientific literacy on genetics topics has increased after being taught using PBL-RQA (Angraini et al, 2023). Similar research was conducted by Leasa et al (2023), which proves that PBL-RQA can improve critical thinking skills in science learning. Therefore, this research aims to determine the effect of PBL-RQA on students' information literacy and selfconfidence.…”
Section: Introductionsupporting
confidence: 60%
“…Thus, elementary school governance is essential. This statistic is important because good school governance will increase good school performance (Leasa et al, 2023). Various empirical studies have found that the performance of schools in Indonesia could be better.…”
Section: Introductionmentioning
confidence: 99%
“…Each phase of PBL interacts with each other, inviting students to build their knowledge with their team members (Tan & Tee, 2021). Leasa et al (2023) explained that PBL had drawbacks for students who did not understand the problem and identified challenges based on the content they learned, making their CT weak. However, it can be overcome by combining PBL with other types of learning.…”
Section: Introductionmentioning
confidence: 99%